Menjembatani Transformasi Masyarakat di Era Society 5.0 - Pilon, Nur'aina; Amane, Ade Putra Ode; Laali, Sri Ayu (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2024)
In the Era of Society 5.0 which is characterized by the integration of advanced technology, the vital role of academics in connecting education, research and innovation for community empowerment is increasingly prominent. Cross-disciplinary integration and cross-sector collaboration play an important role in responding to complex challenges in this context. Academics have a key role in applying their expertise to society's real challenges, supporting a more adaptive transition. Through an inclusive and proactive approach, which includes knowledge transfer, innovation and targeted collaboration, academics have great potential as agents of change to accelerate community empowerment in facing the dynamics of the Society 5.0 Era which is full of challenges. Academics' commitment to broad social roles significantly contributes to shaping a sustainable, inclusive and adaptive future in the Society 5.0 Era. By understanding the main role of academics in empowering society, we are ready to face the complex and changing challenges in the Era of Society 5.0.